On racism and postcolonialism : visual arts and the decolonial, antiracist practice – documentarian, autobiographical approach - Dibba, Seija (My University, 2023)
My MFA thesis work consists of a video installation and a wooden surfboard, that is installed right above it diagonally, in Kuvan Kevät 2022 exhibition, on the second floor of Mylly, in the open space right next to the main staircase. The surfboard has a painted older male face on the side that is visible while viewing the video. The video consists of me narrating an autobiographical story and explaining the reasons that made me paint the surfboard. The surfboard is installed in such a way, that it almost looks like it’s trying to assault the viewers and push them to the ground. On the top side of the surfboard is a spray-tan and a pencil-drawn map of the moles on my (the artist’s) back. Although the story behind the works is autobiographical, it is at the same time connected to a much broader global context, the phenomenons of racism and colonialism. In the video I briefly open up some views into how and why they are so urgent and relevant to me, and then elaborate the context more on the written component. The works intend to be antiracist and decolonial, and the references in the written component add more substance and evidence towards these intentions. I have tried to use tragicomical irony in the symbolism on the choice of visual and material elements. The painted white male face of the surfboard is actually a copy of an online Neanderthal older male face, and the skincolour is the same as the raw aspen surface of the board, the same color as my own skin, as I cannot get tanned, unless it is a fake salon spray-tan. In this way the pieces are also addressing the questionable political positioning of my own skin color, which serves also as an attempt to take responsibility for the structural racism that white-identifying people benefit from by default. Hence it might also be clear, that this violent and unjust privilege is automatic. It is built into global structures and we cannot change it, unless we change these structures. I elaborate more on this by introducing texts on nordic colonial history, the UNESCO Courier declaration of ‘race’ by scientists in 1950, as well as examples of cultural identity politics. I also offer examples of how and why addressing racism and colonialism through artwork, as a white-identifying person, has political standing and how it can also accidentally produce racist work, if there is not a sufficient recognition of one’s own privileges, and how they manifest. The motivation here is call the viewer into antiracist, anticolonialist action, and into exploring their own insecurities in relation to whiteness. I am also interested in how these white privileges function as within global racist, postcolonial structures so effectively, whether we enjoy them or reject them. It was quite difficult to find texts that would have been addressing racism and postcolonialism specifically in the fine arts sector, and for this reason I have mostly addressed these themes through more generalist texts.
Keywords: Visual arts; Postcolonialism; Racism; Anti-racism; rasismi; installaatiot; postkolonialismi; identiteetti; kuvataide; tilataide; kolonialismi; fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|